A low-cost electrochemical thio- and selenocyanation strategy for electron-rich arenes under catalyst- and oxidant-free conditions. Issue 39 (14th June 2018) - Zhang, Xing; Wang, Chenguang; Jiang, Hong; Sun, Linhao
Abstract : A low-cost and efficient thio- and selenocyanation strategy for electron-rich arenes has been developed under constant-current electrolytic conditions in an undivided cell without the use of any catalyst or oxidant. Abstract : A low-cost and efficient thio- and selenocyanation strategy for electron-rich arenes has been developed under constant-current electrolytic conditions in an undivided cell. This strategy is versatile for various (hetero)aromatic compounds such as indole, pyrrole, aniline and anisole under mild conditions without any catalyst or oxidant. Readily available salts NH4 SCN and KSeCN are employed respectively as the sole reagent.